Penerapan Bimbingan Kelompok Dengan Teknik Cinematherapy Untuk Meningkatkan Empati Siswa SMA Negeri 1 Malo - Novitasari, Zeti; Cahyaningrum, Vesti Dwi; Setyoningsih, Yunita Dwi; Susilo, Hintang (Nusantara of Research : Jurnal Hasil-hasil Penelitian Universitas Nusantara PGRI Kediri, 2022)
This study aims to determine the effectiveness of group guidance with cinematherapy techniques to increase students' empathy. The research method used is pre-experimental with a one-group pretest-posttest design. The research subjects were students of class X SMA Negeri 1 Malo for the 2020/2021 academic year. Data were collected through empathy instruments. The data analysis technique used the Wilcoxon test to compare the pre-test and post-test scores. The results of this study indicate that the empathy of class X students of SMA Negeri 1 Malo before being treated with the cinematherapy technique was in the low category with a percentage of 60.36% and after being given treatment with the cinematherapy technique it increased to a high category with an average percentage of 91.08%. The comparison between the results of the percentage of students before and after being given treatment an average of 30.72%. So, it can be concluded that there is a difference between pre-test and post-test, meaning that the group guidance of cinematherapy techniques is effective in increasing empathy for students.